Lights, camera, feminism?: celebrities and anti-trafficking politics - Majic, Samantha (University of California Press, 2023)
"Celebrities in the United States have drawn significant attention and resources to the complex issue of human trafficking-a subject of feminist concern-and they are often criticized for promoting sensationalized and simplistic understandings of the issue. In this comprehensive analysis of celebrities' anti-trafficking activism, however, Samantha Majic finds that this phenomenon is more nuanced: even as some celebrities promote regressive issue narratives and carceral solutions, others use their platforms to elevate more diverse representations of human trafficking and feminist analyses of gender inequality. Lights, Camera, Feminism? thus argues that we should understand celebrities as multilevel political actors whose activism is shaped and mediated by a range of personal and contextual factors, with implications for feminist and democratic politics more broadly"--